2020
DOI: 10.2147/opth.s284844
|View full text |Cite
|
Sign up to set email alerts
|

<p>Icare Home Tonometer: A Review of Characteristics and Clinical Utility</p>

Abstract: The Icare HOME (TA022, Icare Oy, Vanda, Finland) is rebound tonometer recently approved by the US Food and Drug Administration in March 2017 designed for selfmeasurement of intraocular pressure (IOP). IOP remains a major modifiable risk factor for glaucoma progression; however, IOP measurements typically occur through single office measurements on Goldmann applanation tonometry (GAT) and do not always reveal the complete picture of patient's IOP patterns and daily fluctuations, which are important for accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
0
25
1
1
Order By: Relevance
“…Expansion of technology such as home tonometry, home OCT (which have already been developed) and further homebased innovation may allow for increased adoption of virtual visits for glaucoma and retina care, especially for established patients. 5,6 Ophthalmology has previously focused on asynchronous forms of telehealth, such as "store-and-forward" imaging to address workforce shortages, not reduce in-person visits. 7 Our study found that ophthalmologists were not well-equipped to shift care from clinics to patients' homes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Expansion of technology such as home tonometry, home OCT (which have already been developed) and further homebased innovation may allow for increased adoption of virtual visits for glaucoma and retina care, especially for established patients. 5,6 Ophthalmology has previously focused on asynchronous forms of telehealth, such as "store-and-forward" imaging to address workforce shortages, not reduce in-person visits. 7 Our study found that ophthalmologists were not well-equipped to shift care from clinics to patients' homes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In comparing the reliability and reproducibility of IOP values with iCare tonometry, air tonometry and GAT, Valero et al reported ICC > 0.85 and low differences with GAT [ 95 ]. Several studies have reported that iCare provides reproducible and reliability measurements when compared to other tonometers, although it appears to slightly underestimate GAT readings [ 88 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. The repeatability of iCare has been shown to be excellent, with ICC > 0.9 [ 88 , 99 ].…”
Section: Rebound Tonometrymentioning
confidence: 99%
“…IOP readings taken with iCare do not appear to be affected by axial length, refractive error, age and gender [ 87 , 100 ]. GAT and rebound tonometry, however, are influenced by corneal characteristics.…”
Section: Rebound Tonometrymentioning
confidence: 99%
See 2 more Smart Citations